The Laccate Ganoderma of the Southeastern United States: A Cosmopolitan and Important Genus of Wood Decay Fungi - Andrew L. Loyd; Jason A. Smith; Brantlee S. Richter; Robert A. Blanchette; Matthew E. Smith (EDIS, 2017)
Ganoderma Karst. is a large and diverse genus of wood decay fungi that can rot the roots and/or lower trunk of many tree species. There are several laccate (varnished or polished) Ganoderma species that are found in the southeastern United States and this six-page fact sheet provides an overview of the different species. Written by Andrew L. Loyd, Jason A. Smith, Brantlee S. Richter, Robert A. Blanchette, and Matthew E. Smith and published by the Plant Pathology Department.http://edis.ifas.ufl.edu/pp333